Stock Valuation Using the Discounted Cash Flow Method with the Free Cash Flow to Firm Approach: Implications and Impact on Educational Management - Muhammad Athar Maulana; Usep Deden Suherman; Muhammad Sandi Marta (Al-Qalam Institue, 2025)
This research analyzes the fair value of stock using the Discounted Cash Flow (DCF) method with the Free Cash Flow to Firm (FCFF) approach for the period 2020-2024, with implications for educational management. The study employs a quantitative descriptive methodology utilizing secondary data from financial statements and supporting databases. AMRT demonstrated robust financial performance with Gross Profit Margin increasing from 20.3% to 21.5%, Operating Profit Margin improving from 2.2% to 3.4%, and Net Profit Margin rising from 1.4% to 2.7% during the analyzed period. The valuation model projects a Compound Annual Growth Rate (CAGR) of 8.5% for 2025-2029, supported by strategic expansion of 800 new stores annually and digital transformation initiatives. Using a Weighted Average Cost of Capital (WACC) of 11.27%, cost of equity of 12.11%, and terminal growth rate of 5.50%, the DCF analysis yields an enterprise value of RP 114.87 trillion. After adjusting for the net debt position, the intrinsic value per share is calculated at RP 2,420, compared to the market price of RP 2,330, indicating a 3.9% upside potential. The findings suggest AMRT is slightly undervalued, presenting a modest investment opportunity for value-conscious investors seeking exposure to Indonesia's expanding retail sector. The implications of this analysis extend to educational management by highlighting the importance of financial management practices and investment strategies within educational institutions to ensure long-term sustainability and growth.